The safety and efficacy of BCG combined with mitomycin C compared with BCG monotherapy in patients with non-muscle-invasive bladder cancer: A systematic review and meta-analysis - Liu Jianping; Zhou Weijian; Zhang Wei; Chang Congwang; Zhang Peng; Fu Guanghua (Open Medicine)
We sought to determine the efficacy and safety of Bacillus Calmette-Guérin (BCG) combined with mitomycin C (MMC) compared with BCG monotherapy in intravesical therapies for non-muscle-invasive bladder cancer (NMIBC).